School facilities, academic motivation, coping, and resilience their association with student academic achievement in Tacloban City (post-Yolanda) - Francisco, Marie Gabrielle G.; Gabonada, Aimee A. (2015)
The objective of the present study was to examine the relationship between the quality of school facilities, academic motivation-- identified regulation, introjected regulation, intrinsic motivation, and amotivation, coping, and resilience on academic achievement. A sample of 405 elementary pupils from different public elementary schools in TAcloban City were selected, with ages ranging from 9-12 years old. However, 10 questionnaires were excluded from the data analysis due to unanswered items and/or having two or more answers in one item. These students were enrolled in their respective schools in the S.Y.: 2013-14 and were first-hand victims of the Super Typhoon Yolanda.
A correlational analysis was utilized to assess relationship between variables. Results suggest that only introjected regulation r(393)= .121, p=.016, and intrinsic motivation, r(393) = .162, p=.001, were significantly correlated with student academic achievement. It must also be noted that these are the only independent variables which were strongly positively correlated, r (393) = .623, p< 0.05.
Undergraduate thesis (B.A. Psychology)--University of the Philippines, Tacloban
Keywords: Typhoon Yolanda